The crystal structure of catena-poly[aqua-2,2′bipyridine-κ2N,N′-(μ2-5-ethoxyisophthalato-κ 4O,O′:Oʺ,O′ʺ)cadmium(II)] monohydrate, C20H20CdN2O7 - Zhang Lilei; Chang Deming; Dun Mengdan (Zeitschrift für Kristallographie - New Crystal Structures)
C20H20CdN2O7, monoclinic, P21/c (no. 14), a = 9.0154(3) Å, b = 17.7168(8) Å, c = 12.8449(5) Å, β = 98.537(4)°, V = 2028.91(14) Å3, Z = 4, Rgt(F) = 0.0320, wRref(F2) = 0.0715, T = 288.32(10) K.